Refeeding activates neurons in the dorsomedial hypothalamus to inhibit food intake and promote positive valence - Daigo Imoto; Izumi Yamamoto; Hirokazu Matsunaga; Toya Yonekura; Ming-Liang Lee; Kan X. Kato; Takeshi Yamasaki; Shucheng Xu; Taiga Ishimoto; Satoshi Yamagata; Ken-ichi Otsuguro; Motohiro Horiuchi; et al. (Elsevier, 2021)
Objective: The regulation of food intake is a major research area in the study of obesity, which plays a key role in the development of metabolic syndrome. Gene targeting studies have clarified the roles of hypothalamic neurons in feeding behavior, but the deletion of a gene has a long-term effect on neurophysiology. Our understanding of short-term changes such as appetite under physiological conditions is therefore still limited. Methods: Targeted recombination in active populations (TRAP) is a newly developed method for labeling active neurons by using tamoxifen-inducible Cre recombination controlled by the promoter of activity-regulated cytoskeleton-associated protein (Arc/Arg3.1), a member of immediate early genes. Transgenic mice for TRAP were fasted overnight, re-fed with normal diet, and injected with 4-hydroxytamoxifen 1 h after the refeeding to label the active neurons. The role of labeled neurons was examined by expressing excitatory or inhibitory designer receptors exclusively activated by designer drugs (DREADDs). The labeled neurons were extracted and RNA sequencing was performed to identify genes that are specifically expressed in these neurons. Results: Fasting-refeeding activated and labeled neurons in the compact part of the dorsomedial hypothalamus (DMH) that project to the paraventricular hypothalamic nucleus. Chemogenetic activation of the labeled DMH neurons decreased food intake and developed place preference, an indicator of positive valence. Chemogenetic activation or inhibition of these neurons had no influence on the whole-body glucose metabolism. The labeled DMH neurons expressed prodynorphin (pdyn), gastrin-releasing peptide (GRP), cholecystokinin (CCK), and thyrotropin-releasing hormone receptor (Trhr) genes. Conclusions: We identified a novel cell type of DMH neurons that can inhibit food intake and promote feeding-induced positive valence. Our study provides insight into the role of DMH and its molecular mechanism in the regulation of appetite and emotion.